GENZI: Gerakan Edukasi Remaja Sadar Gizi - Aliyah, Nurul; Oktaria, Risma; Putri Septiyani, Kartika; Permata Sari, Intan (Al-Khidmah Jurnal Pengabdian Masyarakat, 2025)
Adolescent girls in boarding school environments are particularly vulnerable to nutritional problems such as Chronic Energy Deficiency (CED) and anemia due to limited food variety, monotonous menus, and insufficient nutrition knowledge. The GENZI (Gerakan Edukasi Remaja Sadar Gizi) program was implemented to strengthen nutrition literacy among female students through anthropometric assessment, individual counseling, group-based education, and the provision of visual media including a balanced-plate nutrition guideline banner. The program involved 82 students from a Madrasah Aliyah in Indralaya. Results indicated that although most students had a normal BMI, a notable proportion were categorized as underweight (22%), overweight (6.1%), obese (4.9%), and at risk of CED (29.3%). Behavioral factors such as low vegetable intake, picky eating, and limited protein options at the boarding school dining facility likely contributed to these conditions. Through interactive education sessions, practical guidance on balanced diets, and personalized counseling, the program successfully improved students’ understanding of adolescent nutritional needs and healthy eating practices within the constraints of the boarding school environment. Findings demonstrate that pesantren-based nutrition education interventions can support behavioral changes and help prevent nutrition-related problems among adolescent girls. Further development of similar programs is recommended, including collaboration with food service managers and long-term monitoring to enhance program effectiveness.